Association of prothrombin, FV Leiden and MTHFR gene polymorphisms in the Montenegrin patients with venous thromboembolism - Teofilov, Sladjana; Magić, Zvonko; Miljanović, Olivera; Ostojić, Tatjana; Bulatović, Milena (Vojnosanitetski pregled, 2021)
Background/Aim. Polymorphisms of the factor V Leiden (FV G1691A), prothrombin (FII G20210A), and methylenetetrahydrofolate reductase (MTHFR C677T) genes are the most commonly investigated inherited risk factors for developing venous thromboembolism (VTE). Despite this fact, there is insufficient data regarding their clinical burden and distribution in the Montenegrin population. The aim of the study was to determine the frequency of these polymorphisms in Montenegrin patients with VTE. Methods. This case-control study was conducted on 160 Caucasian subjects. The study group was composed of 80 patients (35 men and 45 women) with VTE. The control group consisted of 80 healthy individuals (32 men and 48 women) without previous thromboembolic episodes. Genotyping of the FV G1691A, FII G20210A, and MTHFR C677T polymorphisms was performed by allele-specific polymerase chain reaction (PCR). Results. The frequency of heterozygotes (HET) for FII G20210A and FV G1691A was significantly higher in the VTE group compared to the healthy control group (χ2 = 11.7; p = 0.001 and χ2 = 17.69; p < 0.001, respectively). The association of FII G20210A and FV G1691A polymorphisms with an increased risk of VTE [odds ratio (OR) 10.5; 95% confidence interval (CI) = 2.34 to 47.27, and OR 14.8; 95% CI = 3.34 to 65.43; p < 0.001, respectively] was confirmed. Recessive homozygotes (RH) for FII G20210A and FV G1691A were not found in any of the investigated groups. Regarding MTHFR C677T, the difference between the frequency of HET and RH in the control and VTE group was not significant. Conclusion. Our study showed that FII G20210A and FV G1691A polymorphisms are significantly associated with VTE. Detection of the above-mentioned polymorphisms prior to VTE development can contribute to the prevention of further VTE occurrence, especially among patients' relatives who are carriers of these polymorphisms.
Keywords: factor v; genes; mutation; polymorphism, genetic; prothrombin; thromboembolism